1986
DOI: 10.1002/ecja.4410690506
|View full text |Cite
|
Sign up to set email alerts
|

General solution for orthogonal periodic real‐number sequences

Abstract: This paper shows the general solution for the real‐number periodic sequence with an autocorrelation function with zero side lobe, aiming at the application to the spread‐spectrum communication. The general solution is derived by representing the autocorrelation function by a Fourier series and utilizing the components. The solution contains the phase constant. In other words, the sequence and the phase constant are related through the discrete Fourier transform Under the condition that the seqeunce is real, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Although a real-valued orthogonal periodic sequence of period N is normally represented by an amplitude spectrum that is 1 and a phase spectrum that is a discrete Fourier transformation of an odd function [3], here a proposal is shown that utilizes a real-valued shift-orthogonal finitelength sequence of length M = N + 1 to generate the sequence. At first, the following equation represents the aperiodic autocorrelation function of a real-valued shift-orthogonal finite-length sequence of length {a M,l ,i ; i = 0, 1, .…”
Section: Real-valued Orthogonal Periodic Sequence Derived From Real-vmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a real-valued orthogonal periodic sequence of period N is normally represented by an amplitude spectrum that is 1 and a phase spectrum that is a discrete Fourier transformation of an odd function [3], here a proposal is shown that utilizes a real-valued shift-orthogonal finitelength sequence of length M = N + 1 to generate the sequence. At first, the following equation represents the aperiodic autocorrelation function of a real-valued shift-orthogonal finite-length sequence of length {a M,l ,i ; i = 0, 1, .…”
Section: Real-valued Orthogonal Periodic Sequence Derived From Real-vmentioning
confidence: 99%
“…Conversely, if we form an orthogonal periodic sequence of a period N ≥ 8 using periodic partial sequences {b 2,i }, {b 2,i g }, {b 3 …”
Section: Multiplier and Addermentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we propose a generation method of an orthogonal set of real-valued periodic orthogonal sequences of period N = 2 n with positive integer n derived from a realvalued Huffman sequences of length M = 2 ν + 1 with positive integer ν and ν ≥ n. This orthogonal set is included in the set derived from the general solution [4] of real-valued periodic orthogonal sequences, but it is very difficult to generate it by the general solution.…”
Section: Introductionmentioning
confidence: 99%
“…A binary periodic orthogonal sequence which takes 1 or −1 is only (1, 1, 1, −1) of period 4. On the other hand, the general solution of real-valued periodic orthogonal sequences take real numbers has already been proposed [4], and the periodic sequence of various periods can be generated. The real-valued periodic orthogonal sequence of period 2 ν with positive integer ν derived from a real-valued Huffman sequence (shift-orthogonal finite-length sequence) [5], [6] of length 2 ν +1 whose aperiodic autocorrelation function has no sidelobes except at left and right shift-ends exists, has fast correlation algorithm [7].…”
Section: Introductionmentioning
confidence: 99%